CONSUMER INERTIA IN TOILETRIES PRODUCTS: MEDIATION EFFECTS OF QUALITY PERCEPTION ON BRAND CREDIBILITY, BRAND SATISFACTION, AND BRAND COMMITMENT - Pandowo, Aditya; Mamuaya, Nova Christian (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
Inertia is a phenomenon of repeat purchase patterns that consumers unconsciously follow because they are based only on habits. This study explores the phenomenon of inertia by focusing on the stimulants of brand credibility, perceived risk, and brand satisfaction. SmartPLS was used to test the relationship between constructs. A total of 180 respondents were selected using a purposive sampling technique. The results show that brand credibility is an antecedent of perceived quality, brand satisfaction, consumer inertia, and brand commitment. Perceived quality is the beginning of brand satisfaction and commitment. Moreover, brand satisfaction affects consumer inertia. Mediation tests involving perceived quality demonstrate its role as a mediator in the relationship between brand credibility, brand satisfaction, and brand commitment. This study estimates constructs containing consumer inertia by emphasizing the individual cognitive, affective, and conative aspects. The contributions of this study will be helpful for practitioners and academics to explore the determinants of inertia and commitment.JEL: M30, M31.